2003
DOI: 10.1093/bioinformatics/btg1003
|View full text |Cite
|
Sign up to set email alerts
|

Predicting bacterial transcription units using sequence and expression data

Abstract: Our experimental results show that we are able to predict operons and localize promoters and terminators with high accuracy. Moreover, our models that use both sequence and expression data are more accurate than those that use only one of these two data sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…Given the apparent utility of the phylogenetic barcode information in operon prediction, we next sought to develop a statistical framework in which the predictive value of the data could be tested and into which other information sources could also be added. We and others have observed that the operon prediction problem fits well into an HMM framework (4,34), especially because an HMM framework allows us to estimate the confidence with which each prediction is made (as opposed to rule-based prediction frameworks, which generally do not). Accordingly, we adopted this approach in formulating our algorithm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the apparent utility of the phylogenetic barcode information in operon prediction, we next sought to develop a statistical framework in which the predictive value of the data could be tested and into which other information sources could also be added. We and others have observed that the operon prediction problem fits well into an HMM framework (4,34), especially because an HMM framework allows us to estimate the confidence with which each prediction is made (as opposed to rule-based prediction frameworks, which generally do not). Accordingly, we adopted this approach in formulating our algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of the former include methods that rely on microarray-based expression data (3,4,7,26) and others that use different forms of detailed functional annotation (5,30,35). Although these algorithms have shown great promise in terms of being able to predict operon structure with a high degree of specificity and sensitivity, the data they rely on are only available for a select subset of bacterial species, and this limits how widely they can be used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2). k-means clustering was applied 8 with k running from 1 to 16, and the total within-cluster sum of Euclidean distance squares for each clustering was computed. A kink in the sum of squares curve located at a k of 8 indicates that 8 is the optimal number of clusters (32).…”
Section: Strategy For Identifying Genes Regulated By O 2 And/or Fnrmentioning
confidence: 99%
“…Where there are known or predicted polycistronic operons, the other operon members are included for comparison. The transcription start sites are those either predicted by RegulonDB (http:// www.cifn.unam.mx/Computational_Genomics/regulondb/), Bockhorst et al (8), or the Ecocyc database (http://ecocyc.org) or taken from the literature.…”
Section: Strategy For Identifying Genes Regulated By O 2 And/or Fnrmentioning
confidence: 99%